On the solution of (n+1)-dimensional fractional M-Burgers equation - Kilicman, Adem; Shokhanda, Rachana; Goswami, Pranay (Elsevier B.V., 2021)
In the paper, (n+1) -dimensional fractional M-Burgers equation with a force term in the sense of the Caputo fractional derivative is considered. We solve this equation using homotopy perturbation method (HPM) and find its approximate analytical solution. We illustrate the method with some concrete examples. We also provide the graphical representation of the solutions. This paper extends some known results obtained by Sripacharasakullert et al. (2019).